2002
DOI: 10.1029/2001gl014623
|View full text |Cite
|
Sign up to set email alerts
|

Power‐laws and snow avalanches

Abstract: [1] This paper presents evidence of frequency-size power-laws in several groups of snow avalanche paths. Other natural hazards, such as earthquakes and forest fires, exhibit similar power-law relationships. In addition, an analysis of the response of one group of snow avalanche paths to storms through time demonstrates a power-law between the response of the system and the binned frequency of those responses. Our results, as well as our experience with these complex, non-linear systems, are consistent with sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 13 publications
(12 reference statements)
4
36
1
2
Order By: Relevance
“…For example this behavior was found in the eruptions, volcano-induced earthquakes, dikes, fissures, lava flows, and interflow periods of the Piton de la Fournaise volcano by Grasso and Bachélery (1995). Birkeland and Landry (2002) found evidence of frequency-size power-laws in several groups of snow avalanche paths and state that their results are consistent with SOC. They emphasize that the practical implication of this work is that the frequency-size relationship for small and medium sized avalanches may be useful for quantifying the risk of large snow avalanches within a group of avalanche paths.…”
Section: Landslides Wildfires Volcanoes Snow Avalanches Rock-fallsupporting
confidence: 69%
“…For example this behavior was found in the eruptions, volcano-induced earthquakes, dikes, fissures, lava flows, and interflow periods of the Piton de la Fournaise volcano by Grasso and Bachélery (1995). Birkeland and Landry (2002) found evidence of frequency-size power-laws in several groups of snow avalanche paths and state that their results are consistent with SOC. They emphasize that the practical implication of this work is that the frequency-size relationship for small and medium sized avalanches may be useful for quantifying the risk of large snow avalanches within a group of avalanche paths.…”
Section: Landslides Wildfires Volcanoes Snow Avalanches Rock-fallsupporting
confidence: 69%
“…The power-law distribution may be preferable in most cases (Malamud et al, 1996). Recent research has also shown that many other physical phenomena follow a power-law frequency-size distribution (e.g., Ito and Matsuzaki, 1990;Birkeland and Landry, 2002;Malamud et al, 2004). In addition to the form of the scaling relationship used (i.e., exponential, power-law), Burroughs and Tebbens (2005) provide two criteria to determine whether a particular frequency-size distribution can be used for probabilistic forecasting: (1) the scaling exponent (a) should be the same for both short and long time intervals and (2) the scaling relationship from the data excluding the largest events in the catalog should be consistent with those largest events.…”
Section: Analysis Of Empirical Tsunami Datamentioning
confidence: 99%
“…Indeed, the body of evidence supporting power law distributions for extreme natural events is growing: Turcotte (1994) presents case studies from a variety of natural hazards including earthquakes and volcanic eruptions; Scheidegger (1997) provides examples from landslides; Birkeland and Landry (2002) from avalanches; Tzanis and Makropoulos (2002) from earthquakes and Malamud and Turcotte (1999) from forest fires. Hurst et al (1965) provided a classic application of fractal concepts to hydrological processes (the drescaled rangeT for reservoir storage), and recent work in other fields of hydrology has also demonstrated power law relationships within specific ranges, e.g., channel roughness and hydraulic geometry (Bathurst, 2002) and rainfall (Scheidegger, 1997;Gupta and Waymire, 1990;Hubert, 2001;Hubert et al, 2002;Pathirana and Herath, 2002).…”
Section: Models Of Flood Frequencymentioning
confidence: 98%